Self-perceived health and functional status of older people: Telephone-based lifestyle survey of older adults in Tehran province - Masoumeh Sadeghipour Rousari; Moloud Payab; Sahar Keyvanloo shahrestanaki; Mahbube Ebrahimpur; Neda Mehrdad; Solmaz Sadat Naghavi Alhosseini; Faranak Bidmeshgipour; Hossein Adibi; Amirali Safari Astaraei; Raziye Sadat Hosseini; Bagher Larijani; farshad sharifi (Tabriz University of Medical Sciences, 2022)
Background: The prevalence study of health conditions can help policy makers to document base policymaking. This study aimed to reveal the health status, including the prevalence of geriatric syndrome health conditions such as activity of daily livings, pain, and physical and mental health of older adults in Tehran province. Methods: This cross-sectional study was a telephone survey with older people ≥60 years old using a systematic random sampling of telephone numbers in Tehran province. The Persian version of the Katz' activity of daily living (ADL) and the Lawton's instrumental activity of daily living (IADL) questionnaires were used to evaluate the functional status. Pain, history of chronic diseases, continence, hospital admission, sensory problems, and self-perceived health (SPH) were asked by trained nurses or gerontologists thorough telephone interviews. Results: In this study, 1251 older adults with the mean age of 67.03±7.51 years have been recruited. About 64.50% (95% CI: 64.4-64.6) of them were totally independent according to ADL (female=60.02% and male=68.50%), and about 40.50% (95% CI: 40.4-40.5) were independent based on IADL domains (female=39.41% and male=41.80). The dependency rates in ADL increased with the aging of population. Joint pain was the most prevalent type of pains and near to 26.00% (95% CI: 64.4-64.6) of the participants suffered moderate joint pains. About 71.5% (95% CI: 71.4-71.5) of the participants were urinary continent (female=67.66% and male=76.06%), and 91.9% (95% CI: 91.9-92.0) had bowel control (female=91.47% and male=92.94%) and the prevalence of incontinence increased by advancing age. Only 26.70% (95% CI: 26.6-26.8) of the participants reported excellent and good levels of perceived health status (female=21.98% and male=31.48%) and about 26.2% (95% CI: 26.1-26.2) of them reported some degree of visual impairment. Conclusion: The results of the present study can provide a good view about the health profile of older adults, including pain, functional status, sphincter control, chronic diseases, sensory status, and SPH. Future studies should prioritize SPH as an important predictor of mortality rates.